Preferensi Bahan Bakar Minyak Bersubsidi dan Nonsubsidi di Kalangan Pegawai Pemerintah Kota Bandar Lampung - Simanjuntak, Wira Kartua Halomoan; Putra, Sasana; Putri Ofrial, Siti Anugrah Mulya; Sulistyorini, Dr. Rahayu (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2022)
Transportation is defined as the activity of moving passengers and goods from one place to another, in which there is an element of movement. Transportation plays an important role in the development and development of infrastructure in urban areas. This is the main reason for choosing those that are considered efficient in terms of fuel in meeting the transportation needs of the vehicles used. According to the author's observations, people tend to prefer to buy subsidized fuel because of the higher prices. cheap, so willing to wait in long lines and cause the road to be consumed by queues that disturb other road users. Fuel oil itself is divided into 2 groups, namely subsidized and non-subsidized. The problem of adjusting subsidized fuel prices has also developed a discourse regarding who is entitled to subsidized fuel based on Presidential Regulation Number 43 of 2014 as amended by Presidential Regulation Number 43 of 2018 concerning the supply, distribution, and retail selling price of BBM. Data collection was carried out directly in the field by giving questionnaires and asking directly to Bandar Lampung City Government Employees. After that, perform an analytical test by evaluating the tariff according to the ability to buy Ability To Pay (ATP) and the willingness of consumers to buy Willingness To Pay (WTP) using the Analytical Hierarchy Process (AHP) method. From this, the authors are interested in conducting research with the title: "SUBSIDIED AND NON-SUBSIDIED OIL FUEL PREFERENCES IN BANDAR LAMPUNG GOVERNMENT EMPLOYEES".This research begins by collecting literature studies and data, including primary and secondary data. Primary data were obtained through interviews with several respondents using the selected random sampling method. Secondary data sourced from BPS, PT. Pertamina, Bandar Lampung City Government and the results of other studies related to this topic. The data will be used for the next process, namely the analysis of calculations, and the last stage, namely the results and drawing conclusions.Based on the results of the study using the Analytical Hierarchy Process method, it can be concluded that risk is the most influential criterion in selecting the type of fuel oil.Keywords: preferences, subsided and nonsubsided oil fuel